Cross sectional study of health problems in female bidi rollers in Telangana, India - Dr. Suchita N. Kawale; A. Shinde, Manjusha; S. Shinde, Prashant (Public Health Review: International Journal of Public Health Research, 2019)
Introduction: Bidi manufacturing in India is one of the biggest jobs for women in the age-old industry and unorganized sector. Female bidi rollers are exposed to unfiltered tobacco dust and volatile compounds containing hazardous chemicals while making bidis as they do not use any protective wear. Our objective of the study is to find out the health problems in female bidi rollers and suggest preventive strategies. Materials and methods: The present study was a community based cross sectional descriptive study. The study was undertaken in bidi rolling factories of Telangana state. Randomly five bidi factories were selected out of 72 by lottery method and all the female bidi rollers present in the bidi factory at the time of visit were taken as sample size which was 400. Results: The present study shows that maximum number of female bidi rollers 272(68%) were found in the reproductive age group 15-45 years, 240 (60%) belong to socio economic class IV,256(64%) were illiterate and around 248 (62%) of the females were aware about the adverse health effects of bidi rolling. The most common morbidity was pain in shoulder/neck observed in 290(72%) females.176(44%) respondents were suffering from backache/ headache.155(38%) having generalised weakness,112(28%) having cough and 88(22%) having breathlessness. Conclusion: The present study concludes that poverty, illiteracy and ignorance are the main factors forcing female bidi rollers in this harmful occupation. They should be encouraged to use protective material like protective clothing, gloves or masks to avoid harmful exposure to tobacco causing severe health issues.